Determinasi Rendahnya Partisipasi Politik Mahasiswa Ilmu Administrasi Negara UNP dalam Pilkada Gubernur Sumatera Barat 2024 - Ilham Zet, Isratul; Syafril, Rizki (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This research discusses the political participation of students of the State Administration Department of Padang State University (UNP) in the West Sumatra Governor Election in 2024. This research is motivated by the importance of the role of students as agents of change in the democratic process, but in reality their level of participation in regional head elections is still low. The research used qualitative methods with data collection techniques through interviews, observations, and online surveys to active students of the 2019-2024 batch. The results showed that only 37.3% of students exercised their voting rights, while 62.7% chose to abstain. This low participation is caused by several main factors, namely administrative and domicile issues for overseas students, low trust in politics due to rampant cases of corruption and money politics, and the lack of socialization and political education both from the campus and related parties. Many students experience difficulties in arranging a letter of transfer to vote, making them reluctant to participate. In addition, negative perceptions of politicians and unfulfilled promises further strengthen apathy and skepticism among students.